2015
DOI: 10.2967/jnumed.115.157586
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 11C-Laniquidar Kinetics in the Brain

Abstract: Overexpression of the multidrug efflux transport P-glycoprotein may play an important role in pharmacoresistance. 11 C-laniquidar is a newly developed tracer of P-glycoprotein expression. The aim of this study was to develop a pharmacokinetic model for quantification of 11 C-laniquidar uptake and to assess its test-retest variability. Methods: Two (test-retest) dynamic 11 C-laniquidar PET scans were obtained in 8 healthy subjects. Plasma input functions were obtained using online arterial blood sampling with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…As these rate constants are related to transport of [ 11 C]flumazenil across the BBB, this finding supports the notion that [ 11 C]flumazenil is indeed a P-gp substrate, as demonstrated previously in in vivo studies in rodents using both a genetic disruption model and the same pharmacological inhibition model. 3,21 It is also in line with results from an ex vivo study in mice. 4 On the other hand, the comparison between assumed site of seizure onset and contralateral side did not show differences in K 1 /k 2 , and therefore does not provide evidence that P-gp activity is altered at the site of seizure onset in TLE patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As these rate constants are related to transport of [ 11 C]flumazenil across the BBB, this finding supports the notion that [ 11 C]flumazenil is indeed a P-gp substrate, as demonstrated previously in in vivo studies in rodents using both a genetic disruption model and the same pharmacological inhibition model. 3,21 It is also in line with results from an ex vivo study in mice. 4 On the other hand, the comparison between assumed site of seizure onset and contralateral side did not show differences in K 1 /k 2 , and therefore does not provide evidence that P-gp activity is altered at the site of seizure onset in TLE patients.…”
Section: Discussionsupporting
confidence: 82%
“…22 There may be several reasons for the difference in degree of inhibition of flumazenil transport across the BBB after P-gp blockade with tariquidar in humans (23%) than in rodents ($70%). First, in the in vivo rodent studies full P-gp blockade was obtained, 3 whereas this was not possible in the present study in humans, 25 as it was considered unsafe to administer higher tariquidar doses than 2 mgÁkg À1 body weight 25 to patients who also use antiepileptic drugs. Second, species differences in BBB transport of several P-gp substrates have shown a more pronounced increase in cerebral uptake of these substrates after P-gp inhibition in rats than in higher species.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This might be explained by an altered behaviour (as substrate instead of inhibitor) when laniquidar is administered in tracer concentrations. The dosimetry, kinetics and uptake of the tracer have been evaluated in healthy volunteers (Froklage et al 2015;Dörner et al 2011;Postnov et al 2013). These studies showed that [ 11 C]laniquidar generates a high amount of radioactive metabolites that cross the blood-brain barrier.…”
Section: [ 11 C]laniquidarmentioning
confidence: 99%